Investigation of left handed metamaterial in microstrip antenna application - A. Rahim, Mohamad Kamal; A. Majid, Huda (Institute of Electrical and Electronics Engineering (IEEE), 2007)
The speculation and invention of left-handed metamaterial (LH MTM) had sparked the interest of many researchers globally and was said to help increase the gain and directivity of the microstrip antenna. Therefore, the scope of this project was to design, simulate a LH MTM structure in order to proof the claims. The combination of the square rectangular split ring and the thin wire structure was used to obtain the negative value of permeability, mu and the negative permittivity, epsiv. From the simulation done, the gain of the antenna has been increased to 1 dB. This had proven that the focusing effect of the LH MTM really enhance the gain of the antenna.